Who's Afraid of the Boss: Cultural Differences in Social Hierarchies Modulate Self-Face Recognition in Chinese and Americans - Liew, Sook-Lei; Ma, Yina; Han, Shihui; Aziz-Zadeh, Lisa (PLOS ONE, 2011)
Human adults typically respond faster to their own face than to the faces of others. However, in Chinese participants, this self-face advantage is lost in the presence of one's supervisor, and they respond faster to their supervisor's face than to their own. While this “boss effect” suggests a strong modulation of self-processing in the presence of influential social superiors, the current study examined whether this effect was true across cultures. Given the wealth of literature on cultural differences between collectivist, interdependent versus individualistic, independent self-construals, we hypothesized that the boss effect might be weaker in independent than interdependent cultures. Twenty European American college students were asked to identify orientations of their own face or their supervisors' face. We found that European Americans, unlike Chinese participants, did not show a “boss effect” and maintained the self-face advantage even in the presence of their supervisor's face. Interestingly, however, their self-face advantage decreased as their ratings of their boss's perceived social status increased, suggesting that self-processing in Americans is influenced more by one's social status than by one's hierarchical position as a social superior. In addition, when their boss's face was presented with a labmate's face, American participants responded faster to the boss's face, indicating that the boss may represent general social dominance rather than a direct negative threat to oneself, in more independent cultures. Altogether, these results demonstrate a strong cultural modulation of self-processing in social contexts and suggest that the very concept of social positions, such as a boss, may hold markedly different meanings to the self across Western and East Asian cultures.